Play as the Leading Activity of the Preschool Period (Conference Zone, 2022)
The preschool years are an exciting time for young children. When they were infants, they developed a trust of their caregivers. As toddlers, they began to establish some independence. Now, as preschoolers, they use this trust and independence to actively explore new forms of play (e.g., pretend play) and new environments (e.g., school).